Impacto del control interno y la auditoria en la competitividad de las microempresas colombianas (2022)
Internal control and auditing does not guarantee a company the achievement of its objectives, but it does allow it to promote efficiency in operations and encourage adherence to practices ordered by management. For this reason, it is established that an internal control system, designed according to the particular characteristics that distinguish any organization, is one of the fundamental pillars on which the administration can rely to carry out its management. In the present work as main objective we have to argue the impact of internal control for microenterprises in Colombia, which will be developed through three specific objectives, which will provide the necessary information on the main topics for our research and thus achieve using as research methodology a qualitative and interpretive approach, achieving clearly the development of the main research problem.